2023
DOI: 10.17535/crorr.2023.0016
|View full text |Cite
|
Sign up to set email alerts
|

A new search direction for full-Newton step infeasible interior-point method in linear optimization

Behrouz Kheirfam

Abstract: In this work, we investigate a full Newton step infeasible interior-point method for linear optimization based on a new search direction which is obtained from an algebraic equivalent transformation of the central path system. Furthermore, we prove that the proposed method obtains an ε-optimal solution to the original problem in polynomial time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Decomposition cuts were developed in order to extend the concept of concavity cuts for deeper cuts [8,11,12]. Some other relevant research can also be found; see for example [2,4,5,14].…”
Section: Introductionmentioning
confidence: 99%
“…Decomposition cuts were developed in order to extend the concept of concavity cuts for deeper cuts [8,11,12]. Some other relevant research can also be found; see for example [2,4,5,14].…”
Section: Introductionmentioning
confidence: 99%